The Effects of Green Technology, Energy Efficiency and Environmental Concerns to improve Sustainable Environment: Moderating Role of the Organizational Awareness - Ramli, Yanto; Permana, Dudi; Soelton, Mochamad; Yuliantini, Tine; Wibowo, Amirudin; Kartini, Dwi; Ali, Anees Janee (International Journal of Energy Economics and Policy, 2025)
Sustainable environment has the demand of the entire world due to extensive environmental degradation and this aspect needs the foremost intention of recent studies. Thus, the present study investigates the impact of green technology, energy efficiency and environmental concerns on sustainable environment in Indonesia. The study also investigates the organizational awareness as moderator among predictors and predictive variables. The study gathered the primary data with the help of survey questionnaires form the employees of the oil industry in Indonesia. The study also used the smart-PLS to examine the association between the constructs. The outcomes indicated that the green technology, environmental concerns and energy efficiency has a positive and significant association with sustainable environment. The results also revealed that the organizational awareness also moderate the association among green technology, environmental concerns, energy efficiency and sustainable environment. The study provides the guidelines to the policymakers in making significant policies related to achieve the sustainable environment using energy efficiently, high concerns of environment and effectively using green technology.